Integrating major ion geochemistry, stable isotopes (18O, 2H) and radioactive isotopes (222Rn, 14C, 36Cl, 3H) to understand the interaction between catchment waters and an intermittent river - Zibo Zhou; Ian Cartwright; Uwe Morgenstern; L. Keith Fifield (Science of The Total Environment, 2024)

Cosmogenic exposure dating constraints for coastal landslide evolution on the Island of Malta (Mediterranean Sea) - Mauro Soldati; Timothy T. Barrows; Mariacristina Prampolini; Keith L. Fifield (Journal of Coastal Conservation, 2018)

Sediment mixing at Nonda Rock: investigations of stratigraphic integrity at an early archaeological site in northern Australia and implications for the human colonisation of the continent - Bruno David; Richard G. Roberts; John Magee; Jerome Mialanes; Chris Turney; Michael Bird; Chris White; L. Keith Fifield; John Tibby (Journal of Quaternary Science, 2007)
Archaeological excavations in sediments dating to between 60 000 and 40 000 years ago are rare in Australia. Yet this is precisely the period in which most archaeologists consider that Aboriginal people arrived on the continent. In the few cases where such early sites have been investigated, questions have invariably been raised as to the reliability of stratigraphic associations between cultural items and the surrounding sediments. This paper describes a method for examining sediment mixing in a stratigraphic sequence using the optically stimulated luminescence (OSL) signals from individual sand‐sized grains of quartz. We apply this method to the archaeological site of Nonda Rock (north Queensland), in combination with radiocarbon dating of charcoal fragments, to construct chronologies for human occupation and for the preceding, culturally sterile, deposits. Our age estimates have implications for the timing of first human arrival in Australia. Copyright © 2007 John Wiley & Sons, Ltd.

Holocene evolution of the granite based Lizard Island and MacGillivray Reef systems, Northern Great Barrier Reef - Siwan A. Rees; Bradley N. Opdyke; Paul A. Wilson; L. Keith Fifield; Vladimir Levchenko (Coral Reefs, 2006)